After the Kanjuruhan Disaster: The influence of loyalty, sport involvement, and perceived risk by football fans to return to the stadium - Saputra, Angga; Baharuddin, Ghalib; Mu'ammal, Immanuel; Aprilia, Putri Dwi; Fatimah, Ghadis Nur (Journal Sport Area, 2025)
Background: The sustainability of football tourism is greatly influenced by supporters’ visits. After the Kanjuruhan stadium disaster, in terms of their loyalty to the club, the risks they perceived as a result of the disaster, and and involvement of fans to the sport there was a question about whether football fans (Aremania) wanted to visit the stadium again. Research Objectives: This study explores sports fans’ intention to revisit stadiums, a topic rarely studied compared to the more common focus on tourism destinations. This study  aims to determine the effect of loyalty, sports involvement and risk perception on revisit intentions. Methods: Quantitative explanatory research has been carried to test the influence of loyalty, sport involvement and perceived risk on revisit intention. The respondents in this study were 533 Aremania in Malang, Indonesia. then the data obtained was analyzed using WARP-PLS 7.0. Findings and Results: The results of this research show that loyalty and sports involvement influence revisit intention, meanwhile perceived risk does not influence revisit intention. Conclusion: Aremania still shows the intention to watch the match live at the Kanjuruhan stadium and this desire is influenced by their loyalty to the club. Apart from that, Aremania tends to dare to take risks by watching matches at the Kanjuruhan Stadium. Research on revisit intention at sports stadiums has rarely been conducted before. This research has benefits as a basis for government consideration to create a safe system so as to revive the sports tourism sector such as improving management and security measures at the stadium. This research has a scientific contribution as a source of reference in further research, especially from the aspect of sport tourism regarding consumer behaviour to make revisit intention.